PI3-Kinase p110α Deficiency Modulates T Cell Homeostasis and Function and Attenuates Experimental Allergic Encephalitis in Mature Mice - José M. Rojo (International Journal of Molecular Sciences, 2021)
Class I phosphoinositide 3-kinases (PI3K) are involved in the development of normal and autoimmune responses, including Experimental Autoimmune Encephalomyelitis (EAE), a mouse model for human multiple sclerosis (MS). Here, the role of the ubiquitously expressed class IA PI3K p110α catalytic subunits in EAE has been analyzed using a model of Cre/flox mediated T cell specific deletion of p110α catalytic chain (p110αΔT). Comparison of two month-old (young) and six month-old (mature) p110αΔT mice and their wild type (WT) counterparts indicated loss of spleen CD4+ T cells that increased with age, indicating a role of p110α in their homeostasis. In contrast, CD4+ T regulatory (Treg) cells were enhanced in mature p110αΔT mice when compared to WT mice. Since Myelin Oligodendrocyte Glycoprotein (MOG) peptide-induced EAE is dependent on, or mediated by CD4+ T cells and CD4+ T cell-derived cytokines and controlled by Treg cells, development of EAE in young and mature WT or p110αΔT mice was analyzed. EAE clinical symptoms and disease scores in six month p110αΔT mice were significantly lower than those of mature WT, or young WT and p110αΔT mice. Furthermore, ex vivo antigen activation of lymph node cells from MOG immunized mature p110αΔT mice induced significantly lower levels of IFN-γ and IL-17A than young p110αΔT or young and mature WT mice. Other cytokines including IL-2, IL-10 or TNF-α showed no significant differences between p110αΔT and WT mature mice. Our data show a lower incidence of MOG-induced EAE in mature p110αΔT mice linked to altered T cell homeostasis and lower secretion of inflammatory cytokines.